Measuring Debilitating and Facilitating Anxiety Within Nursing Simulation - Janet M. Reed; Tracy Dodson; Lynette Phillips; Amy Petrinec (Nursing Reports)
Background: Anxiety in simulations can be influenced by various factors that either motivate or immobilize students. Understanding simulation anxiety is crucial for educators to design appropriately challenging scenarios without overwhelming students. No instruments have yet been tested to differentiate between debilitating and facilitating anxiety within nursing simulations. Methods: A quantitative repeated measures design was used to examine students’ baseline and pre-simulation anxiety with 90 pre-licensure junior level nursing students. The Achievement Anxiety Test (AAT) was administered to differentiate levels of debilitating and facilitating anxiety. Results: The revised AAT demonstrated preliminary validity and reliability for measuring debilitating and facilitating anxiety when used in nursing simulation. Linear regression showed only debilitating anxiety significantly predicted pre-simulation state anxiety. Baseline anxiety has a significant impact on students, increasing debilitating anxiety in simulated settings. Conclusions: To ensure success in practice settings, it is important to address students baseline anxiety to support a successful transition into practice. This study was prospectively determined to be exempt with the University’s Institutional Review Board on 6 December 2022 and was not prospectively registered in a formal registry.